The Fourth Crusade and Its Consequences for the Medieval Bulgaria: Kaloyan, the Latins and the Greeks (1204–1207) - Gjuzelev, Vassil (Studia Ceranea, 2013)
The analysis of the Bulgarian-Latin relations between 1204 and 1207, i.e. in the second half of Tsar Kaloyan’s reign, leads to conclusions as follows: 1. the Bulgarian monarch played a major role in forcing the newly-created Latin empire to adopt a defensive policy in the political struggles in the Balkan Peninsula; 2. thus, the Tsar contributed to retaining and, in consequence, consolidating the remnants of the Byzantine empire (Nicaea, Epirus-Thessalonica); 3. in the Byzantine memory the actions of Kaloyan were evaluated negatively, as times of plundering the Byzantine territories and relocations of its population into Bulgaria; 4. for the later Bulgarian historiography the Tsar’s wars with the Latins were of secondary significance, and despite the official union with the Roman church he was remembered as a defender of the Orthodox faith.